Ageing in the right place – a prototype of a web-based housing counselling intervention for later life. (18th May 2020) - Granbom, Marianne; Szanton, Sarah; Gitlin, Laura N.; Paulsson, Ulrika; Zingmark, Magnus
Abstract: Background: Despite a strong desire among most older adults to age in place, there are few widely available services to support planning and preparing for one's future housing needs. Objective: To develop a prototype of a web-based housing counselling intervention for use in later life, by employing a user-centred design. Material and Methods: As the first step in intervention development, we employed a development process based on research circle methodology. Nine older adults participated in three sessions. Findings from literature reviews, a meeting with a technology and design panel ( n = 6) and interviews with representatives of nonprofit organizations, companies, and municipalities ( n = 7) served as discussion points. Result: An on-paper prototype was derived, composed of the THINK, LEARN and ACT module reflecting different stages of the decision-making process. Each module addressed preferences, health, home and social and financial resources. Key design features and theoretical underpinnings were included. Conclusion and Significance: A user-centred design process can result in services that are aligned with older adults' preferences for obtaining housing information. Services for planning and preparing future housing needs have the potential to increase older adults´ well-being at home as well as reduce costs for care and housing provision by the municipalities.